Analysis of micrograph and material properties of gas welded butt joints of mild steel plate. (2020) - Kumar, Shrawan; Dwivedi, Vijay K.
Abstract: Mild steel was weld by use of Gas welding. To examine the Micrograph and analyse mechanical properties of the V-joint. The mechanical properties of gas weld from parent metal of V-joint was found to be enhanced. Gas welding is getting the most out of welding process for Mild Steel (MS). The sizes of the specimens are 55 mm × 50 mm × 6 mm and notch at 45 0 made on the specimen.